SCAPHOIDAL MEGALOURETHRA: A RARE CASE PRESENTATION - Hidianingsih, Septiani; Yudha, Andre (Indonesian Urological Association, 2020)
Objective: To propose reduction urethroplasty as a technique for urethral reconstruction for scaphoidal megalourethra. Case(s) Presentation: A male child with the age of one year and four months was known to suffer from megalourethra when dorsumcision was done. The procedure was done starting with marking sutures at the penile gland. Disclose the penile skin as proximal as possible. When disclosed, identify the urethra and dilation was seen so as a finger could be inserted for around 2 centimeters. Urethra was incised, then excise the excess urethral tissue, suturing was done based on the 6F Folley catheter to the point where the urethra dilates. After Folley catheter was inserted, inversion suture was done on the urethra with PDS 6.0 and glanulopasty with PDS 6.0. After evaluation, urethral lumen was found not narrowed, skin was sutured with PDS 6.0. Cystostomy was inserted to divert urine and maintained until one week post-operation. Discussion: Cosmetic and functional results were good and satisfactory. Patient could urinate with no hindrance. Post-operation complication was not found. However, erectile function was difficult to obtain in pediatric patients. Conclusion: Megalourethra is a rare case that needs appropriate diagnosing and management to prevent complication. Operation technique of reduction urethroplasty was done as the chosen management for scaphoidal megalourethra. Furthermore, more in depth research with better methodology was needed to determine the outcome of patients with megalourethra.